Application of Operating Room Nursing Intervention to Incision Infection of Patients Undergoing Gastrointestinal Surgery Can Reduce Complications and Improve Gastrointestinal Function - Wang, Ping; Chen, Hong; Ji, Qi (Frontiers in Surgery, 2022)
【Abstract】 Objective: To observe the influence of nursing intervention in operation room on incision infection of patients undergoing gastrointestinal surgery and the improvement of gastrointestinal function. Methods: Total of 340 patients who underwent gastrointestinal surgery in our hospital from June 2020 to August 2021 were included. According to the random number table, they were divided into the conventional nursing group (n=170) and the operating room nursing group (n=170). The routine nursing group was treated with routine nursing intervention, while the operation nursing group was treated with operating room nursing intervention. The incision infection, healing, gastrointestinal function recovery and complications in the two groups were compared, and the patient care satisfaction was recorded. Results: The incidence of incision swelling, pain and incision secretion in the operating room nursing group was significantly lower than that in the conventional nursing group (P<0.05). The patients in the operating room nursing group had higher grade A healing than that in the conventional nursing group, and lower grade B and grade C healing than that in the conventional nursing group (P<0.05). The time of anal exhaust, the first defecation and the time of gastric tube removal in the operating room nursing group were lower than those in the conventional nursing group (P<0.05). The incidence of postoperative complications such as incision infection, incision dehiscence, early inflammatory bowel adhesion and abdominal abscess in the operating room nursing group was lower than that in the conventional nursing group (P<0.05). The total satisfaction degree in the operating room nursing group was significantly higher than that in the conventional nursing group (P<0.05). Conclusion: Nursing intervention in operation room can reduce complications and improve gastrointestinal function when applied to patients undergoing gastrointestinal surgery due to incision infection.